The remainder is 3 when we need to divide ![6x^4-3x^5+2x^3+x-3\,\,by \,\,x+1](https://tex.z-dn.net/?f=6x%5E4-3x%5E5%2B2x%5E3%2Bx-3%5C%2C%5C%2Cby%20%5C%2C%5C%2Cx%2B1)
Step-by-step explanation:
We need to divide
and find the remainder
Dividing:
The division is shown in figure below:
The quotient is:![-3x^4+9x^3-7x^2+7x-6](https://tex.z-dn.net/?f=-3x%5E4%2B9x%5E3-7x%5E2%2B7x-6)
The remainder is: 3
So, The remainder is 3 when we need to divide ![6x^4-3x^5+2x^3+x-3\,\,by \,\,x+1](https://tex.z-dn.net/?f=6x%5E4-3x%5E5%2B2x%5E3%2Bx-3%5C%2C%5C%2Cby%20%5C%2C%5C%2Cx%2B1)
Keywords: Division of Polynomials
Learn more about Division of Polynomials at:
#learnwithBrainly
4b=a then plus 10 to see if the age holds true to 3b=a in ten years. Then since the question is how old is she today? You must either add 6 to young age (of20) or minus 4 from the older (of 30).
So Betty would be 26 today.
0.5x - 2 < 5.5
Add 2 to both sides.
0.5x < 7.5
Now divide by 0.5 on both sides.
x < 15
Answer:A.) triangular prism B.) triangular-based pyramid
Step-by-step explanation:
Answer:
p = ½ (x₁ + x₂)
q = a (x₁x₂ − ¼ (x₁ + x₂)²)
Step-by-step explanation:
y = a (x − x₁) (x − x₂)
Expand:
y = a (x² − x₁x − x₂x + x₁x₂)
y = a (x² − (x₁ + x₂)x + x₁x₂)
Distribute a to the first two terms:
y = a (x² − (x₁ + x₂)x) + ax₁x₂
Complete the square:
y = a (x² − (x₁ + x₂)x + ¼(x₁ + x₂)²) + ax₁x₂ − ¼ a(x₁ + x₂)²
y = a (x − ½ (x₁ + x₂))² + a (x₁x₂ − ¼ (x₁ + x₂)²)
Therefore:
p = ½ (x₁ + x₂)
q = a (x₁x₂ − ¼ (x₁ + x₂)²)